Greenhouse Gas Emission from Rice field in Indonesia: Challenge for future research and development - Miranti Ariani; Eko Haryono; Eko Hanudin (Faculty of Geography, Universitas Gadjah Mada, 2021)
Rice is an essential crop in Indonesia. Any aspects of rice to increase productivity have been well studied and documented; however, there are still lacking well-documented studies on its environmental aspects, including climate change. Many researches might already be conducted, but only a few have been published in a peer-reviewed journal. There is still a lack of robust data on greenhouse gas (GHG) emissions from the rice field in Indonesia, factors affecting and the technology on how to reduce it. From the reviewed publications, it was found out that research only conducted under a controlled environmental setting. More research on understanding the controlling factors (e.g., water management, rice cultivar, soil types, and fertilizer) of GHG emission from rice field is still needed. The result will introduce a sustainable farming practice, with low in GHG emissions, high in productivity, simple to apply and generate more income to farmers. This review has identified the gaps for future research and development in Indonesia. The research should meet the need, either national or global strategies. Development of a new farming practice will succeed in the presence of government policies. Therefore an intensive interdisciplinary approach between researcher and other stakeholders should be conducted.